The development of organizational, legal and ideological formation of the institutions providing insurance services - Klapkiv, Yurii (Herald of Economics, 2019)
The article considers the nature of insurance services and a variety of organizational and legal forms of institutions that provide these services. A new formulation for mutual insurance societies is suggested, taking into account existing forms of such institutions in various countries. It is brought to light that insurance business developed from reciprocal needs, or reciprocity. Later on insurance became a financial service aimed at meeting the needs of one party and receiving financial gain by another party. Particular attention is paid to forms of exercising insurance at an emerging stage of the market of insurance services.The principle of reciprocity is highlighted, and its general framework is described. Reciprocity is defined as a basis for promotional and reciprocal insurance. It is proposed to divide institutions according to ownership property into joint-stock partnerships and mutual insurance societies. Their advantages, disadvantages and special features in various countries are specified. A special focus is given to reciprocity which is based on consolidation of customers and their risks.It is concluded that insurance companies in the form of joint-stock partnerships have one more target for activities, which is making profits for stockholders. Furthermore, the research paper describes organizational and legal forms of institutions that can provide insurance services in the EU countries and Ukraine, as well as types of joint-stock partnerships in these countries.A comparative analysis of requirements for the authorized capital of institutions providing insurance services in Ukraine and the EU is carried out. It is found that in many countries these requirements are differentiated for mutual insurance societies and joint-stock insurance companies.In contrast to liberalized access of insurance services to markets in different countries, requirements for financial stability and for size of insurance companies have been steadily tightening. This stimulated the consolidation of both joint-stock insurance companies, particularly in Ukraine, and mutual insurance societies in European countries.It is emphasized that requirements for the amount of authorized capital and stability of an insurance institution are indirectly interdependent.